2003
DOI: 10.2527/2003.812416x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ractopamine on the behavior and physiology of finishing pigs12

Abstract: The objectives of this study were to examine the effects of ractopamine (RAC) on the behavior and physiology of pigs during handling and transport. Twenty-four groups of three gilts were randomly assigned to one of two treatments 4 wk before slaughter: finishing feed plus RAC (10 ppm) or finishing feed alone. Pigs were housed in the same building in adjacent pens with fully slatted floors and ad libitum access to feed and water. Behavioral time budgets were determined in six pens per treatment over a single 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
62
4
11

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 16 publications
10
62
4
11
Order By: Relevance
“…Plasma concentration of cortisol was determined using a competitive binding radioimmunoassay kit (Marchant-Forde et al, 2003;GammaCoat, DiaSorin, Stillwater, MN, USA). A Multi Species Leptin Ria kit (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma concentration of cortisol was determined using a competitive binding radioimmunoassay kit (Marchant-Forde et al, 2003;GammaCoat, DiaSorin, Stillwater, MN, USA). A Multi Species Leptin Ria kit (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…In this size of experiment, it is difficult to conclude that these DOAs and condemns were due to the RAC, or were a random effect; however, since we have no way of excluding these animals based on treatment, they are assumed to be due to the RAC treatment. Previous research suggests that RAC pigs may be more susceptible to stress during shipping (Marchant-Forde et al 2003). This particular experiment was carried out at PSC Elstow Research Farm, which is located less than 1 h travel time from the abattoir.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with low doses of RAC over increasing periods are scarce. Moreover, production animals are constantly submitted both to chronic stress by confinement and handling, such as acute stress by transport and slaughter (Marchant-Forde et al 2003), which could make the results of this study important. Information regarding the potential use of RAC on metabolic parameters has been highlighted in several studies, but information about the behavior is still infrequent.…”
Section: Introductionmentioning
confidence: 99%
“…Information regarding the potential use of RAC on metabolic parameters has been highlighted in several studies, but information about the behavior is still infrequent. Studies with pigs fed with RAC demonstrated changes in pig's behavior (Marchant-Forde et al 2003;Poletto et al 2010). Other studies have demonstrated the influence of beta-adrenergic agonists on rodent's behavior (Flicker and Geyer 1982;Gorman and Dunn 1993).…”
Section: Introductionmentioning
confidence: 99%